The Effect of Entrepreneurship Education on Entrepreneurial Intention of University Students by Adopting Linan Model - Buana, Yud; Hidayat, Desman; Prayogi, Budi; Vendy, Vendy (Binus Business Review, 2017)
The success of entrepreneurship education programs remains unanswered if it is associated with some students who have decided to launch and pursue a business venture. It is important to know the intentions of a nascententrepreneur to start up the business ventures persistently if experts and policy makersâ attentions are drawn on how to arouse interest in starting a business. Quantitative approached was used in this research to examine the influence of entrepreneurship education, social norms and self-efficacy on intentions to pursue business ventures by adopting Linan model of intention-behavior. The model was addressed to the students who participated in entrepreneurship education program during the mid of study in Bina Nusantara University. Last, the result is in line with Linan model.